Factors to Decline of Legislatures: a Study In Indian Context: Exploring the Causes of Parliamentary Decline in India (Journal of Advances and Scholarly Researches in Allied Education, 2015)
India's founders saw parliament as an institution thatwould provide social and political unity. They adopted a first‐past‐the‐post electoralsystem which enabled the Congress Party to dominate legislative politics forthree decades. The overlapping nature of the ruling party and the governmentcaused parliament to serve primarily as a public forum for the ventilation ofgrievances rather than a law‐makingbody. The decline of Parliament is, indeed, a worldwide phenomenon, but evenmore striking in India. In India, except for brief periods, a single party wasthe majority in both Houses of Parliament. Thus party bosses have had much moresay in policy matters than Parliament as such. This paper discusses the majorfactors to decline of legislatures